Ages of Life : Living and Aging in Conflict?. - Kriebernegg, Ulla (transcript Verlag, 2014)
The binary construction of »young± and »old±, which is based on a biogerontological model of aging as decline, can be redefined as the ambiguity of aging from a cultural studies perspective. This concept enables an analysis of the social functions of images of aging with the aim of providing a basis for interdisciplinary exchange on gerontological research. The articles in this publication conceive the relationship between living and aging as a productive antagonism which focuses on the interplay between continuity and change as a marker of life course identity: aging and growing older are pro.
Keywords: Aging -- Social aspects.; Gerontology.; Older people -- Social conditions.; Aging in literature.; Vieillissement -- Aspect social.; Gérontologie.; Personnes âgées -- Conditions sociales.; Vieillissement dans la littérature.; gerontology.; SOCIAL SCIENCE / Gerontology; Aging in literature; Aging -- Social aspects; Gerontology; Older people -- Social conditions